Proceedings of EcoComfort 2020 - Blikharskyy, Zinoviy; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
This book gathers the latest innovations and applications in the field of resource-saving technologies and advanced materials in civil and environmental engineering, as presented by leading international researchers and engineers at the 2nd International Scientific Conference EcoComfort and Current Issues of Civil Engineering, held in Lviv, Ukraine on September 16-18, 2020. It covers a diverse range of topics, including ecological and energy-saving technologies; renewable energy sources; heat, gas and water supply; microclimate provision systems; innovative building materials and products; smart technologies in water purification and treatment; protection of water ecosystems; and architectural shaping and structural solutions. The contributions, which were selected using a rigorous international peer-review process, highlight exciting ideas that will spur novel research directions and foster multidisciplinary collaborations.
Keywords: Buildings$1 (BDesign and construction.s; Building; Construction; Engineering, Architectural; Sustainable development; Renewable energy resources; Building materials; Building Construction and Design; Sustainable Development; Renewable and Green Energy; Building Materials